Socio-behavioral risk factors among older adults living with HIV in Thailand - Patou Masika Musumari (2018)
© 2017 Musumari et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: There has been a global increase in HIV infection in persons 50 years of age and older. This group is at risk for development of chronic illness that may be exacerbated by socio-behavioral risk factors such as smoking, unhealthy alcohol use, and sedentary lifestyle. However, socio-behavioral risk factors in this older HIV infected population are not well described. The current study aims to describe and document factors related to alcohol use, tobacco smoking, and physical exercise in older adults living with HIV (OALHIV). Methods: This cross-sectional quantitative study was conducted between August and September 2015, and enrolled HIV-infected participants aged 50 years and older from 12 community hospitals in Chiang Mai Province, Northern Thailand. Results: Of the 364 participants recruited in the study, 57.1% were female, and 67.3% were between 50–59 years of age. Respectively, 15.1%, 59.1%, and 18.7% were current smokers, currently engaged in physical exercises, and reported ever drank alcohol in the past year. 22.1% of those who drank alcohol reported experience of heavy episodic drinking. Male gender was one of the strongest predictors of ever drank alcohol in the past year (AOR, 4.66; CI, 2.28–9.49; P<0.001) and of being a current smoker (AOR, 13.41; CI, 7.23–24.87; P<0.001). Lower household income was associated with increased odds of ever drank alcohol in the past year (household income (1 USD = 35 THB) of ≤ 5,000 Baht versus > 20,000 Baht: AOR, 5.34; CI, 1.28–22.25; P = 0.021). Lower educational level was associated with decreased odds of physical exercises (no education versus secondary and higher: AOR, 0.22; CI, 0.08–0.55; P = 0.001). Conclusion: Smoking and alcohol use is common among OALHIV, with a substantial proportion not engaging in physical exercises. Interventions for OALHIV should particularly target males and those of lower socio-economic status to deter smoking and alcohol use and to promote physical exercises.